REFLEKSI BUDAYA LUBUKLINGGAU DALAM KUMPULAN CERPEN BULAN CELURIT API KARYA BENNY ARNAS - Diah Irawati; Harris Effendi Thahar; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this study was to describe the reflection of Lubuklinggau Malayan culture in the short stories Bulan Celurit Api by Benny Arnas based on (1) the religious system, (2) the system of tools and equipments of life, (3) The system of livelihood, (4) social system. The data of this research were words, expressions, phrases and sentences which pointed on the religious system, the system of tools and equipments of life, the system of livelihood and social system in the short stories Bulan Celurit Api by Benny Arnas. The data were collected through content analysis. The finding of this research was the short stories Bulan Celurit Api by Benny Arnas which reflected the social life in Lubuklinggau today and past situation. Kata kunci: Refleksi, Budaya, Lubuklinggau, Sistem